Leader-Member Exchange and Organisational Performance: A Review of Communication, Biases, and Personality Challenges - Willie, Michael Mncedisi (Manunggal Halim Jaya, 2025)
This study investigated how high-quality Leader-Member Exchange (LMX) relationships influence organizational performance, focusing on open communication, personal biases, and personality clashes in shaping these relationships and their outcomes. An empirical literature review was conducted by searching databases such as JSTOR, PubMed, and Google Scholar for articles related to LMX theory, communication, biases, and personality clashes. Peer-reviewed articles from recent decades were reviewed through abstracts and full texts, with the thematic analysis used to synthesize the findings. High-quality LMX relationships, characterized by trust, mutual respect, and open communication, significantly enhance organizational performance. These relationships lead to greater job satisfaction, team member engagement, and productivity, as well as support Organisational Citizenship Behaviours (OCB) and proactive behaviors, fostering innovation and collaboration. However, personal biases, the underutilization of skilled personnel, failure to recognize potential talent, and inadequate succession planning were identified as factors that could hinder effective communication and overall organizational performance. Organizations should improve LMX relationships by enhancing communication, addressing biases through targeted training, and implementing strategic talent management. Recognizing and developing potential talent, aligning roles with skills, and establishing clear succession plans are essential for optimizing leader-subordinate interactions and boosting organizational performance. This study provides a detailed review of how high-quality LMX relationships affect organizational performance. It emphasizes the importance of communication and addressing biases and personality clashes to enhance leadership effectiveness and organizational success.